Social Media Marketing Strategy to Promote Sustainable Tourism in Bantaeng Shallot Farms - Yulianti, Nadya; Achmadi, Nila Sartika; Ananda, Fajar Tri; Wangania, Caroline Nathania Priscilla; Agustina, Alya; Nurfadillah, Nurfadillah (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to develop a comprehensive strategy for managing shallot farms in Desa Bonto Lojong as a sustainable tourism destination. The shallot farms have faced significant challenges due to the negative impact of viral content on social media, resulting in substantial losses for the farmers. To mitigate these effects, the farm owners have implemented measures such as installing fences to control visitor access. However, these temporary solutions do not address the underlying issues of sustainable tourism development. Using a qualitative research design with observation and Focus Group Discussion (FGD) methods, this study focuses on the social media marketing strategy, utilizing the 4Ps of marketing product, place, price, and promotion to promote the shallot farm as a sustainable tourism destination. The research aims to identify the potential of shallot farms as a tourist attraction while ensuring that the development is sustainable and beneficial for both the local community and the environment. The findings will provide insights into transforming shallot farms into sustainable tourism destinations, enhancing their economic viability while preserving ecological and social integrity. This study contributes to the body of knowledge on sustainable tourism development by highlighting community-based initiatives and the role of social media in promoting local agricultural products. The outcomes will be beneficial for policymakers, local stakeholders, and farmers, providing practical strategies to manage and promote their agricultural products sustainably.